The Effect of Collaborative Problem Solving Learning Model on Mathematical Literacy Skill - S Morin; S Prabawanto (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
This research aims to investigate the difference in mathematical literacy skills between students who experienced collaborative problem solving learning and those experiencing expository learning. The research used quasi experimental method with Only Control Design post-test research design. Subject in this research was the entire eighth grade students of junior high school in Tangerang City. In this research, there were two groups, namely experimental group which consisted of 36 students and control group involving 36 students. Data collection techniques used in this research was purposive random sampling through the use of instrument on mathematical literacy skills test in the form of essay. Based on the research results, it was found that mathematical literacy skills of the students who received the learning experience of collaborative problem solving are better than the skills of students who experienced the expository learning.